Tahlīlu kullīyati al-jaudah al-idārīyah (TQM) li al-‘amalīyāti al-idārīyati al-tasygīlīyati fī daurah al-lugah al-arabiyah al-Azhār Pare - Wahyuni, Septi; Maulidi, Yuana; Fauzi, Muhammad Maftuh (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
The changes within globalization are very dynamic and difficult to be predicted. For this reason it requires an organization or institution to provide maximum service. In this, Indonesia should be prepared for different strategies in various working areas. One of them is the implementation of Integrated Quality Management or also known as Total Quality Management (TQM). There are many key terms related to the study of Total Quality Management such as joint improvement and quality improvement i.e. continuous quality improvement. In this research, the researcher focuses on how to analyze Total Quality Management (TQM) in operational management witihin the Arabic language course Al-Azhar. This study aimed to determine the extent of applying TQM in the Al-Azhar course in improving the quality of students. This study implemented the qualitative research. To collect data, the researcher used interviews, notes, field notes, and documentation which includes personal documents, official documents, and data sources. The results of this study suggested that the floral cycle Barry carried out the total quality management in some of these ways such as; first, the customer value strategy, providing value to customers including product characteristics, delivery methods, and services; secondly, the organizational systems theory, focusing on providing value to customers; third, the theory of quality improvement, emphasizing on how to deal with the constantly changing external environment, especially the changing tastes of customers.